Pathogenesis mechanisms employed by Alternaria species - Gohar Taj,; PD Meena,; Priyanka Giri,; Dinesh Pandey,; Arvind Kumar,; Anil Kumar, (Journal of Oilseed Brassica, 2026)
Alternaria species are mainly saprophytic fungi, but some have acquired pathogenic capacities causing plantdiseases over a broad host range. More than 70 phytotoxins are produced by them from which only a smallproportion have been chemically characterized and reported to act as mycotoxins. Host-selective toxins(HSTs) produced by Alternaria plant pathogens are generally low-molecular-weight secondary metaboliteswith a diverse range of structures that function as effectors controlling pathogenicity or virulence in certainplant–pathogen interactions. This review summarizes all the diseases caused by Alternaria spp., mycotoxinsproduced by Alternaria spp. and the recent advances in elucidating mode of action of host specificAlternaria toxins at physiological, biochemical and molecular levels